Brucellosis in Iranian buffalo: Prevalence and diagnostic methods - Maryam Dadar; Gamal Wareth; Heinrich Neubauer (German Journal of Veterinary Research)
The water buffalo (Bubalus bubalis) in Iran represent an important source of meat and milk products with high biological value. Given the importance of water buffalo in Iran and the prevalence of brucellosis as one of the most important zoonotic diseases in this ruminant species, this study summarized available data on history, epidemiology, diagnosis, and control of brucellosis in water buffalo from previous studies that have been carried out in Iran. According to the documented data, there are three main groups of Iranian buffalo, including the Khuzestan ecotype (Khuzestan province); the Azary ecotype (Western/ Eastern Azarbaijan and Ardabil provinces); and the North ecotype (Gylan and Mazandaran provinces). Preliminary studies conducted on Iranian buffaloes either by serological or molecular tools reported that buffaloes\' infection occurred due to natural exposure to a wild strain of Brucella abortus and Brucella melitensis. Previous studies dealing with brucellosis in Iranian buffalo are next to none. This review notifies the importance of reliable and detailed epidemiological investigations of Iranian buffaloes through continuous monitoring systems of the health status of buffalo populations. Continuous test and slaughter strategy, vaccination, and re-planning of veterinary activities are required to mitigate buffalo\'s role in disseminating and maintaining brucellosis in Iran